Green growth pathway through green innovation and human capital under low and high regime: From the perspective of energy intensity - Abdullah Abdulmohsen Alfalih (Journal of Project Management)
Green growth has recently become an interesting field of research, as the pairing of economic growth and environmental preservation is seen as an urgent need. Despite this importance, few studies have investigated the underlying factor of green growth (GG), especially those relating to green innovation (GI) and human capital (HCI) as catalysts of energy intensity (IE). The current study aims to investigate the repercussions of human facets and the green patents on energy intensity-driven green growth. We use the panel threshold regression (PTR) supported by the Exponential Panel Smooth Regression (EPSR) method spanning the period 1997-2019 to the case of 16 countries which include most and least eco-friendly countries. Our findings disclosed that below a threshold value of the human capabilities, green technological innovation remains without negative effects on EI. Our results also revealed that only the group of most eco-friendly countries (MEFC) is those which benefit from green innovation by moving from a low to high regime of human capital index. The group of least eco-friendly countries (LEFC) cannot benefit from green innovation to foster GG even by translating from low regime to high regime. In addition, human capital exerts an adverse effect on EI in the case of low regime; and therefore, for a low threshold value of the HCI. The outcomes of the present study can clarify the need to implement future action plans in terms of arbitration between the environmental quality in its different forms and savings in terms of energy consumption.